2016
DOI: 10.1016/j.jafrearsci.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of lateritic soils in the construction/development of sustainable housing in Africa: A geological perspective

Abstract: Highlights• Appraisal of the previous work in the use of tropical soils in low cost, energy efficient housing development.• It established CEBs as sustainable building materials for a sustainable environment.• Identification of lateritic soils as suitable material in the production of CEBs.• Established the importance of parent rock material (its type and mineralogy) in strength and durability of CEBs.• Discouraging the common practice of firing clay bricks for the sake of sustainable environment. AbstractLate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“…A high clay content will not be acceptable due to high expected shrinkage in CEB"s produced from such soils. Although stabilisation with lime has been suggested for soils with more than 35% clay, it may not be economical (Houben and Guillaud 1994;Oyelami and Van Rooy 2016). The soil index properties were found to have a significant influence on brick strength at a 10% level of significance as estimated through the F-test while the plasticity index was found significant at 5% which reflects a strong influence on the strength of bricks ( Table 4).…”
Section: Consistency Of Soil and Its Impact On Strength Of Bricksmentioning
confidence: 94%
See 3 more Smart Citations
“…A high clay content will not be acceptable due to high expected shrinkage in CEB"s produced from such soils. Although stabilisation with lime has been suggested for soils with more than 35% clay, it may not be economical (Houben and Guillaud 1994;Oyelami and Van Rooy 2016). The soil index properties were found to have a significant influence on brick strength at a 10% level of significance as estimated through the F-test while the plasticity index was found significant at 5% which reflects a strong influence on the strength of bricks ( Table 4).…”
Section: Consistency Of Soil and Its Impact On Strength Of Bricksmentioning
confidence: 94%
“…The effect of grain size distribution is reflected on the brick strength (Table 6), It was found that lateritic soils derived from the schist belt region (OS) tend to give higher brick strengths due to the specific particle size distribution (higher amount of fines), amount of stabiliser added i.e. 5% and more importantly, the load at compression (compaction pressure) (Adam and Agib 2001;Oyelami and Van Rooy 2016). Based on the fact that a low pressure manual mould was used, the load at compression depended partly on the effort of the human operator.…”
Section: Sc-clayey Sand Sm-silty Sandmentioning
confidence: 99%
See 2 more Smart Citations
“…Various research projects on the Development of locally available building materials have been undertaken. In order to preserve and preserve the environment, the use of environmentally friendly building materials, commonly known as green building materials, must be promoted to promote the idea of sustainable construction [2]. One of these green building materials is adobe [3].…”
Section: Introductionmentioning
confidence: 99%